Боротьба української діаспори за багатокультурність Канади (1962–1971) - Круковський, В. (Народна творчість та етнологія, 2019)
Переломним моментом в інтеграції української діаспори в суспільно-політичне та культурне життя Канади стало запровадження в державі політики багатокультурності. Делегати VII Конгресу українців Канади 1962 року звернулися до державної влади з проханням усіляко сприяти зрівнянню прав українців Канади з тими, які мають англо- та франко-канадські спільноти в галузі освіти, культури й мистецтва. У резолюції форуму порушувалися питання про впровадження вивчення української мови в канадських школах і університетах, збільшення кількості українських студентів. 19 липня 1963 року федеральний уряд Канади призначив Королівську комісію двомовності та двокультурності, покликану дослідити проблему загострення протистояння англо-франко-канадців та запропонувати шляхи її вирішення. 3 березня 1964 року у верхній палаті федерального парламенту сенатор Павло Юзик виголосив промову «Канада: багатокультурна нація», у якій він зазначив, що держава в етнічному розумінні складається не лише з англо- і франко-канадців, але й із «третього елементу». Ідеться про аллофонів – представників національних меншин країни, які живуть переважно в західних регіонах. Першим успіхом Комітету українців Канади стало порозуміння із провінційним урядом Квебеку, коли українці визнали французьку спільноту як першопоселенців на цій території і погодилися на французьку як державну мову. Тим часом прем’єр-міністр провінції Жан Лесаж 3 жовтня 1965 року на зустрічі з керівниками КУК у Вінніпегу офіційно підтримав позицію про Канаду як радше багатокультурну, аніж двокультурну державу, тим самим ввівши україномовне навчання в початкових класах, де набиралася відповідна кількість учнів. У 1970 році провінційні парламенти всіх степових провінцій, зокрема Манітоби та Альберти, прийняли закони, за якими шкільні ради мали можливість запроваджувати двомовне англо-українське навчання. 8 жовтня 1971 року прем’єр-міністр Канади П. Трюдо виклав у Палаті громад парламенту засади нової політики багатокультурності. На Х Конгресі українців Канади, що відбувся 8–11 жовтня 1971 року, він наголосив на важливості засад політики не лише для українців Канади, а й для всього канадського суспільства загалом, підкреслюючи той факт, що представники КУК сприяли перетворенню країни в багатокультурну державу. The introduction of multiculturalism policy in the state has become the turning point in the Ukrainian Diaspora's integration into the social, political, and cultural life of Canada. The delegates of the VII Congress of Canadian Ukrainians in 1962 have appealed to the state authorities to promote the equalization of the rights of Canadian Ukrainians with those of the Anglo-Canadian and French-Canadian communities in the fields of education, culture, and art. The problem of the introduction of Ukrainian language study at Canadian schools and universities to increase the number of Ukrainian students has been raised in the forum resolution. On July 19, 1963, the federal government of Canada appointed the Royal Commission on Bilingualism and Biculturalism to investigate the problem of the exacerbation of Anglo-French Canadians and suggest ways to solve it. Since the commencement of its work, the CUC has deployed brigades, which have represented and defended in all Canadian centers, insisting that multiculturalism better characterizes the real situation in the country. And its society is formed not only by two ethnocultural communities. On March 3, 1964, in the upper house of the federal parliament, Senator Paul Yuzyk enunciated the speech Canada: a Multicultural Nation. He has noted that the state in the ethnic sense consists not only of Anglo- and French-Canadians but also of the third element: it refers to allophones—representatives of national minorities of the country, who live mainly in western regions. The first success of the Canadian Ukrainians Committee consists in the understanding with the provincial government of Quebec when the Ukrainians recognized the French community as the settlers in the area and agreed to French as a state language. Meanwhile, the prime minister of the province, Jean Lesage, on October 3, 1965, at a meeting with the CUC leaders in Winnipeg, has officially supported the position of Canada as a rather multicultural than bicultural state, thereby introducing Ukrainian-language teaching in primary schools, where the corresponding number of students is taken. In 1970, the provincial parliaments of all steppe provinces, in particular Manitoba and Alberta, decreed laws enabling school councils to introduce bilingual English-Ukrainian education. On October 8, 1971, Prime Minister of Canada P. Trudo stated the foundations of a new policy of multiculturalism in the House of Commons. At the X Congress of Canadian Ukrainians, held on October 8–11, 1971, he has emphasized the importance of policy principles not only for Ukrainians in Canada but also for the entire Canadian society on the whole, emphasizing the fact that the CUC representatives have contributed to the country's transformation into a multicultural state.